• Rearrange first equation
x + 2y = 9
• Multiply the first equation by 3
3(x + 2y = 9)
• Rewrite equation 1
3x + 6y = 27
• Write both equations
3x + 6y = 27
3x - 6y = -15
• Subtract equation 1 from equation 2
3x + 6y = 27
-
3x - 6y = -15
• Write the reaming values
12y = 42
• Divide both side by 12 to solve for y
12y = 42 ➗ 12
• Write value of y
y = 3.5
• Substitute the value of y into one of the original equations
2(3.5) = -x + 9
• Use algebra and sole for x
7 = -x + 9
x = 9 - 7
x = 2
• Write final point
(3.5, 2)